ANALYTICAL CALCULATION OF BENDING ELEMENTS WITH BASALT FIBER REINFORCEMENT AND GLASS COMPOSITE ROD UNDER SHORT-TERM DYNAMIC LOADING (Spectrum Journal of Innovation, Reforms and Development, 2023)
During the construction and operation of buildings and structures, in addition to static loads, short-term dynamic impacts caused by explosions, accidents, etc. may occur on building structures and their elements. As a result, damage or destruction of structures may occur, which leads to possible casualties and significant material losses. Taking into account the influence of such impacts on the load-bearing capacity of building structures is relevant. A significant number of works by domestic and foreign authors are devoted to methods for calculating the bending of reinforced concrete elements under static and short-term dynamic loading. In the vast majority of cases, the object of research is flexural concrete elements with steel rod and/or fiber reinforcement. The issues of predicting and assessing the stress-strain state of bending concrete elements reinforced with glass-composite reinforcement and/or basalt fiber under short-term dynamic loading have not been sufficiently studied. Current building codes and regulations provide for the calculation of such elements only under the influence of static loads.